2020
DOI: 10.1111/irv.12712
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti‐NS1 antibodies after pandemic influenza exposure: Evaluation of a serological method for distinguishing H1N1pdm09 infected from vaccinated cases

Abstract: Background: Reliable exposure information is crucial for assessing health outcomes of influenza infection and vaccination. Current serological methods are unable to distinguish between anti-hemagglutinin (HA) antibodies induced by infection or vaccination. Objectives:We aimed to explore an alternative method for differentiating influenza infection and vaccination. Methods: Sera from animals inoculated with influenza viruses or purified H1N1pdm09HA were obtained. Human samples were selected from a pregnancy coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The Luciferase Immunoprecipitation system (LIPS) assay allows for a comprehensive understanding of the antibody immune response against infectious agents (17) by the expression of any protein or antigen as a recombinant Renilla luciferase (Ruc)-antigen fusion. The LIPS technique has previously been used to distinguish infected versus vaccinated cases for influenza due to the presence of antibodies against non-structural proteins (18), and to characterize human infections by zoonotic spill over from bat viruses (19). In this study, we used LIPS to assess the acute and convalescent antibody responses to a panel of 15 potential SARS-CoV-2 antigens: the 4 structural proteins (S, N, M and E), 3 S subunits (S1, S2, S2’), the 7 available ORFs (ORF3a, 3b, 6, 7a, 7b, 8 and 10) and 1 relevant NSP within ORF1a/b (NSP1) (20).…”
Section: Introductionmentioning
confidence: 99%
“…The Luciferase Immunoprecipitation system (LIPS) assay allows for a comprehensive understanding of the antibody immune response against infectious agents (17) by the expression of any protein or antigen as a recombinant Renilla luciferase (Ruc)-antigen fusion. The LIPS technique has previously been used to distinguish infected versus vaccinated cases for influenza due to the presence of antibodies against non-structural proteins (18), and to characterize human infections by zoonotic spill over from bat viruses (19). In this study, we used LIPS to assess the acute and convalescent antibody responses to a panel of 15 potential SARS-CoV-2 antigens: the 4 structural proteins (S, N, M and E), 3 S subunits (S1, S2, S2’), the 7 available ORFs (ORF3a, 3b, 6, 7a, 7b, 8 and 10) and 1 relevant NSP within ORF1a/b (NSP1) (20).…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that NanoLIPS offers a highly sensitive and simple technique for the detection of Ag-specific Abs present in sera from mouse, macaque, and tree shrew. In recent years, LIPS has been widely used for assessing immune responses in infectious diseases caused by HIV (36), Ebola virus (37), and influenza virus (38). In a previous study, a binding Ab titer against HA-1 of influenza virus, measured via Renilla luciferase-based LIPS, demonstrated a positive correlation with HI-determined titer.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the full length NS1 protein of A/WSN/1933 (H1N1) influenza virus on the cell surface was previously described [20]. It is also known that the natural influenza infection in animals [30,31] or people [19] may result in the formation of NS1 specific antibodies indicating the presentation of this antigen to B-lymphocytes in the extracellular compartment. The formation of antibodies to NS1 protein may serve as indirect evidence of its release from the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since NS1 protein can interact with the RNP complex [18], it is possible to assume that both of them may be delivered to the cell surface in association. Indirect confirmation of this hypothesis is the detection of anti-NS1 antibodies in sera from humans with laboratory-confirmed influenza [19]. In addition, it was demonstrated that nonstructural antigens are detected on the surfaces of the cells infected with influenza A virus [20].…”
Section: Introductionmentioning
confidence: 90%